Modified conjoint fascial sheath suspension for the correction of severe congenital blepharoptosis in pediatric patients at different ages - Wang, Huixing; Liu, Zhaochuan; Li, Yadi; Song, Lihua; Pang, Runhui; Yang, Jianwei; Bai, Ping (Frontiers in Pediatrics, 2022)
Objective To evaluate the surgical outcomes of modified combined fascia sheath (CFS) and levator muscle (LM) complex suspension for the correction of severe congenital blepharoptosis in pediatric patients. Methods Pediatric patients with severe congenital blepharoptosis were enrolled form July 2017 to July 2021. All patients were divided into two groups according to their age (group A ≤ 7 years; group B > 7 years) and received CFS + LM suspension surgery. Main surgical outcome indexes include margin reflex distance 1 (MRD1) and MRD1 regression. Postoperative complications such as lagophthalmos (LAG), conjunctival prolapse, exposure keratopathy and trichiasis were documented. Results Fifty patients (60 eyes) were enrolled, including 17 patients (18 eyes) in group A and 33 patients (42 eyes) in group B. The MRD1 in group A was 3.06 ± 0.64 mm at 6 months after the operation, and the MRD1 in group B was 2.64 ± 0.69 mm 6 months postoperatively which is significantly lower than that of group A (P = 0. 044). At the last visit, however, the MRD1 in group A was 3.00 ± 0.69 mm and the MRD1 in group B was 2.64 ± 0.70 mm. There was no significant difference in MRD1 between two groups in long term (P = 0.255). Additionally, there were a variety of degrees of MRD1 regression, especially in the first month after the operation in both groups (both P < 0.001). Moreover, there were 9 cases of postoperative complications in group A and 13 cases in group B. The overall occurrence of postoperative complications in group A was significantly lower than that in groups B (χ2 = 4.413, P = 0.036). Conclusions CFS + LM suspension, a modified CFS-based surgery, is an effective treatment for severe congenital blepharoptosis in pediatric patients. Moreover, CFS + LM suspension demonstrate excellent long-term outcomes, including good movement of the eyelid, satisfied eyelid closure and fewer postoperative complications.